Program and Portfolio Affordability Tradeoffs Under Uncertainty Using Epoch‐Era Analysis. Issue 1 (13th September 2016) - Vascik, Parker D.; Ross, Adam M.; Rhodes, Donna H.
Abstract: The design, acquisition and stewardship of large scale, sociotechnical programs and portfolios faces new challenges as constituent systems evolve in sophistication and interconnectedness, all while exogenous factors become more volatile. However, advances in computational capabilities and uncertainty modeling better enable systems engineers to evaluate value tradeoffs in early phase conceptual design. This paper extends prior work that explored system design tradespaces for affordability under uncertainty to the program and portfolio level. Time‐varying exogenous factors, such as resource availability, stakeholder needs, or technology obsolescence may influence value contribution of constituent systems over the lifecycle of a portfolio, potentially making an initially attractive design less attractive over time. This paper introduces a method to conduct portfolio design for affordability by leveraging Epoch‐Era Analysis with aspects of Modern Portfolio Theory. The method is demonstrated through the design of a carrier strike group portfolio involving the integration of multiple legacy systems and newly acquired vessels.